STUDY ON HIGH-FREQUENCY FATIGUE PROPERTIES OF PVD TiCrAlN COATING OF CUTTING TOOL - WANG NingChang; LIU QingFeng; CHENG Xin; JIANG Feng; XU XiPeng (Jixie qiangdu)
Based on ultrasonic vibration-assisted mode,high-frequency impacting tests with diamond indenter at different amplitudes on TiCrAlN coating of cutting tool are carried out. The microstructure and morphology are obtained by scanning electron microscopy（ SEM） and 3D profiler. The failure mechanism of coating under impacting is analyzed. The high frequency fatigue property of the coating is analyzed. The results show that: lateral crack could be seen under impacting test; the maximum tensile stress occurs close the edge of the contact zone of impact center; TiCrAlN coating is easy to emerge the fatigue damage under the high-frequency impact loading,and the adhesion strength of the coating and substrate interface affects the impact fatigue strength of cutting tool coating.